2004
DOI: 10.5081/jgps.3.1.251
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Wide Area Augmentation System for Ionospheric Storm Events

Abstract: Abstract.One of the greatest challenges in developing accurate and reliable satellite-based augmentation systems (SBAS) is modeling of ionospheric effects. Wide area GPS networks are generally sparse (station spacings of 500-1000 km), and ionosphere models can suffer degraded performance in regions where large spatial gradients in total electron content (TEC) exist. Of particular concern for Wide Area Augmentation System (WAAS) users is the feature called storm enhanced density, which is associated with large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
1
20
0
3
Order By: Relevance
“…Such large TEC gradients may have a profound impact on radio communication and navigation systems [Ledvina et al, 2002;Doherty et al, 2004;Skone et al, 2004;Coster and Skone, 2009;Sun et al, 2013] and therefore motivate continued study of the SED/trough evolution and generation mechanisms.…”
Section: à2mentioning
confidence: 99%
“…Such large TEC gradients may have a profound impact on radio communication and navigation systems [Ledvina et al, 2002;Doherty et al, 2004;Skone et al, 2004;Coster and Skone, 2009;Sun et al, 2013] and therefore motivate continued study of the SED/trough evolution and generation mechanisms.…”
Section: à2mentioning
confidence: 99%
“…Firstly, because ionosphere models can suffer degraded performance in regions where large spatial gradients in TEC exist. Secondly, because the observed feature of storm-enhanced density, associated with large TEC gradients at mid-latitudes, is a significant source of error in the SBAS correction models (Skone et al, 2004). It is therefore reasonable to conclude that such conditions can be specified successfully by space weather forecasting techniques based on real-time data availability in conjunction with mathematical algorithms to extrapolate to near-future conditions (Wilkinson, 2006).…”
Section: Article In Pressmentioning
confidence: 98%
“…Large magnetic storms with Dst < À100 nT have been found to cause intense ultra-high frequency (UHF) scintillation in the Wide Area Augmentation System (WAAS) which is to provide GPS based navigation to aircraft. For instance, Skone et al (2004) observed large WAAS errors in the region of strong electron density enhancement during the October and November, 2003 geomagnetic storms. Geomagnetic storms of different magnitudes (based on magnetic indices such Kp and Dst) have been observed to produce different effects on TEC at different latitudes.…”
Section: Introductionmentioning
confidence: 97%